Report of the proceedings at a general court of the Governor and Company of Adventurers of England trading into Hudson's Bay [electronic resource] : held at the City Terminus Hotel, Cannon Street, London, on Monday, 15th July, 1895 : Sir Donald A. Smith, K.C.M.G. (the governor), presiding. - Hudson's Bay Company.; Strathcona and Mount Royal, Donald Alexander Smith, Baron, 1820- 1914. ([London : s.n., 1895)
Caption title. At head of title : Hudson's Bay Company. Electronic reproduction. Mode of access: Internet. 44